Meningkatkan Kemampuan Mengenal Huruf Hijaiyah Melalui Media Pohon Huruf dengan Metode Demonstrasi pada Anak Usia Dini - Anis Suwarni; Hadi Machmud; La Hewi; Laode Anhusadar; Erdiyanti Erdiyanti (Diniyah: Jurnal Pendidikan Dasar, 2022)
This study aims to improve the ability to recognize hijaiyah letters through the media of letter trees by using demonstration methods. This study used classroom action research conducted at Nusa Indah Kindergarten, Wolasi, Konawe Konsel Regency. The research sample is class B at the age of 5-6 years. The research process was carried out in two cycles, each cycle consisting of two meetings and four stages in each, namely: planning, implementing, observing and reflecting. The results showed that through the media of letter trees using the demonstration method could improve the ability to recognize hijaiyah letters in class B children at Nusa Indah Kindergarten, Wolasi, South Konawe.Keywords: Recognizing hijaiyah letters, early childhood, letter tree